HISTOCHEMICAL ESTIMATION OF H2O2 AND ANTIOXIDANT RESPONSE OF DIFFERENT BRASSICA VARIETIES UNDER CR STRESS SOIL - F. Ajmal; A. Zulfiqar; Firdaus-e-Bareen; S. Asghar; K. Shakeel; M. Ahmed (Journal of Animal and Plant Sciences, 2022)
Four varieties of Brassica were used as heavy metal accumulator to clean up the chromium (Cr) contaminated soil. A pot experiment was conducted with completely randomized design (CRD) containing four treatments and three replicates. Different concentrations of Cr content, i.e. 50%, 30% and 10% contaminated soil were used. Plant cells continuously produce Reactive Oxygen Species (ROS). However, increased accumulation of ROS occurred under abiotic stress. Qualitative detection of H2O2 was done by using 3, 3ʹ-Diaminobenzidine (DAB) that produced reddish brown spots on the surface and veins of leaves. Quantitative estimation of H2O2 (%) was measured by DPPH radical scavenging assay in four varieties of Brassica. Among four treatments, maximum DPPH radical scavenging activity by antioxidants occurred in T0 with 0% Cr. Amount of Chlorophyll was assessed by standard procedure. By using standard protocols enzymes antioxidants (superoxide dismutase, catalase, ascorbate peroxidase and lipid peroxidation) activity was determined. This study aimed to investigate the histochemical estimation of H2O2 and response of different enzymatic antioxidants as a defense against ROS in the mechanism of Cr stress tolerance in Brassica.
Keywords: Antioxidant enzymes; H2O2; ROS; Cr stress; Phytoremediation